2011
DOI: 10.1590/s0102-86502011000200002
|View full text |Cite
|
Sign up to set email alerts
|

Studies of distribution and recurrence of Helicobacter spp. gastric mucosa of dogs after triple therapy

Abstract: Purpose:To analyze the triple antimicrobial therapy in positive Helicobacter spp. dogs and to investigate recurrence. Methods: A total of 20 dogs underwent endoscopy followed by gastric biopsy using the rapid urease test and histopathology stained with Giemsa. Ten animals were treated with triple therapy recommended for humans and divided into control and experimental group. The control group was kept in isolation while the experimental group was placed in contact with positive animals during 60 days. Results:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 23 publications
(30 reference statements)
3
6
0
Order By: Relevance
“…Although, a previous study has shown that triple therapy for seven days using clarithromycin, amoxicillin and lansoprazole was effective in 100% of dogs (Anacleto et al 2011), in human medicine, therapies of shorter duration are no longer recommended since it has been demonstrated that a 14-day triple therapy has an approximately 12% better cure rate than a 7-day therapy (Vilaichone et al 2006). Our study confirms this finding in dogs.…”
Section: Discussionsupporting
confidence: 83%
“…Although, a previous study has shown that triple therapy for seven days using clarithromycin, amoxicillin and lansoprazole was effective in 100% of dogs (Anacleto et al 2011), in human medicine, therapies of shorter duration are no longer recommended since it has been demonstrated that a 14-day triple therapy has an approximately 12% better cure rate than a 7-day therapy (Vilaichone et al 2006). Our study confirms this finding in dogs.…”
Section: Discussionsupporting
confidence: 83%
“…In dogs, while many studies reported that the fundus and body present higher bacteria density and higher probability to find Helicobacter spp. [8,49,50] others found no significant differences between the density of NHPH in the fundus, body and antrum [31,[51][52][53][54]. The discrepancies in the results regarding the spatial distribution of Helicobacter spp.…”
Section: Discussionmentioning
confidence: 93%
“…Replacing sucralfate with famotidine, omeprazole, or bismuth subsalicylate may also be effective (Marks, 1997;Jenkins and Bassett, 1997;DeNovo and Magne, 1995). Recurrence rates within 60 days of treatment can be as high as 80% (Anacleto et al, 2011). Treatment of enterohepatic helicobacters may depend on species susceptibility.…”
Section: E Helicobacteriosismentioning
confidence: 99%